STRATEGI ADAPTASI PETANI PALA DI DESA DAME KECAMATAN SIAU TIMUR KABUPATEN SITARO - Dinding, Grace M. (Universitas Sam Ratulangi, 2013)
Agriculture as the main livelihood in human life has undergone a long process of development in the history of human culture. Siau people in the village especially Dame in this case choosing farming as a way or the type of activity chosen in the procurement of goods or goods and services to meet their needs, is also driven by the circumstances and the type of resource that can be used on the natural environment in place they live. How they sustain life while geographically around the volcano is Mount Karangetang. This need for adaptation strategies that farmers strive to try to manage and survive in environmental conditions. Nutmeg crop and thus has a strategic role to support people's lives for the better, at least this plant has two main roles in human life, both economically and environmentally. To make ends meet before harvest time the farmers in the village of Dame nutmeg using adaptation strategies to seek livelihood sideline as motorcycle taxis, baggage workers and farm laborers. Keywords: peasants, culture, adaptation